(untitled) (MIST International Journal of Science and Technology, 2023)
Concrete is one of the most used manufactured materials in the world. Fly ash (FA) is a byproduct produced from pulverized coal combustion in power generation. A total of 0.08 million tons of class F fly ash is produced from a coal-based power plant yearly in Barapukuria, Bangladesh, whose disposal is of a great issue. Therefore, this study aims to explore the possibility of using class F FA in concrete construction as a supplementary cementitious material. In this study, two different water-to-cement ratios (0.4 and 0.5), each with five cement replacement levels numerically, 0%, 10%, 20%, 30%, and 40% with FA are used. Various tests are performed on cylinder and beam specimens to assess physical, mechanical, and durability properties, such as workability, density, compressive strength (CS), splitting tensile strength (STS), flexural strength (FS), chloride ion penetrability (CIP), and shrinkage. Analyzing the results, it is reported that workability increases and density decreases with the increasing FA replacement. Mechanical properties mostly decrease with increasing FA content. However, the strength gained with age is higher for concrete with FA compared to the control concrete. The CIP reduces with FA replacement, especially at 56 days of age. Shrinkage value reduces 82% at 40% replacement FA replacement and w/c ratio 0.4. However, at 10% FA replacement and concrete age of 56 days, mechanical strength loss is infinitesimal or even better compared to the control concrete. Thus, a low replacement percentage of FA with a high curing period is a suitable concrete cement alternative. MIJST, Vol. 11, December 2023 : 27-41 DOI: https://doi.org/10.47981/j.mijst.11(02)2023.430(27-41)